Analysis of Communication Management Factors on Rework in Toll Road Construction Projects - Tri Ardhietama; Budi Susetyo (Green Publisher Indonesia, 2026)
Rework is one of the main sources of inefficiency in construction projects because it has an impact on increasing costs, time, and material usage. In toll road projects that have linear work characteristics and involve many stakeholders, rework is often triggered by ineffective communication management. This study aims to identify the communication management factors that cause rework in toll road projects, and determine the dominant factors that cause it, assess the risk level of rework based on the frequency of occurrence and cost impact. The research method uses a quantitative approach through expert validation and surveys of respondents to the Jakarta-Merak Section project, multiple linear regression analysis, descriptive analysis, and risk analysis based on PMBOK® 6th Edition. The results showed that the failure factors of the three components of communication management, namely, planning, management, and monitoring of communication had a significant effect on rework (p-value < 0.05) with a simultaneous contribution of 55.5%. Ten dominant factors were successfully identified, with the main factors being specifications and less detailed working drawings that triggered design adjustments. Then the rework Wrisk analysis showed an average risk score of 0.060 which was in the low risk category. The findings of this study confirm that the effectiveness of communication management has a central role in minimizing rework in toll road projects. Improving the quality of document planning, clarity of communication flows, and information monitoring are needed to reduce the occurrence of rework and improve the efficiency of project resource use.